BRYOZOAN FAUNAS IN THE MIDDLE MIOCENE OF HUNGARY: BIODIVERSITY AND BIOGEOGRAPHY - Moissette P.; Dulai A.; Müller P. (My University, 2006)
A study of the Badenian (Middle Miocene) marine deposits of Hungary yielded a rich bryozoan fauna of 238 species comprising 59 cyclostomes, 176 cheilostomes, and 3 ctenostomes. Six palaeobiogeographic groups have been identified among this fauna on the basis of the present-day and fossil distribution of the species. Similarities within the Central Paratethys and between the Central Paratethys, the Mediterranean and the Atlantic have then been calculated using Jaccard's index. The results indicate strong affinities between the Central Paratethyan basins of Hungary, Austria, Poland, and Romania. The higher number of species and the lower level of endemism observed in Hungary is explained by the vicinity of this basin to the entrance of the water seaway connecting the Mediterranean to the Paratethys. A decrease in taxonomic diversity between the Early and the Late Badenian is also observed, accompanied by the absence of most tropical taxa from the Late Badenian. This points towards a less optimal climate and a more pronounced isolation of the Badenian sea from the oceanic waters. The major result of the comparative study between Central Paratethyan and Mediterranean bryozoan faunas is the presence of numerous common species. The number of endemic Paratethyan species is however relatively high, indicating that the bryozoan faunas of both seas evolved in a relative isolation. The exchange of faunas between the Mediterranean and the Paratethys was probably regulated by an anti-estuarine circulation permitting an easier incursion of Mediterranean species into the Paratethys, but hindering the Paratethyan endemics from entering the Mediterranean. The stronger affinity between Hungarian and Mediterranean faunas also shows that this basin was closer to the entrance of the water seaway connecting the two areas and thus the Mediterranean species entered more easily. The similarity index between Central Paratethys and Atlantic faunas is much lower than with the Mediterranean. This indicates that the palaeobiogeographic domain formed by the Mediterranean and the Paratethys was relatively homogeneous during the Middle Miocene and that the relationships with the Atlantic were weaker. Exchange of benthic organisms between the Central Paratethys and the Indo-Pacific during the Middle Miocene is considered here as extremely improbable. © 2005 Elsevier B.V. All rights reserved.
Keywords: BADENIAN; BIODIVERSITY; BIOGEOGRAPHY; BRYOZOANS; CENTRAL PARATETHYS; HUNGARY; MIDDLE MIOCENE; Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен